Discovery and modulation of diterpenoid metabolism improves glandular trichome formation, artemisinin production and stress resilience in Artemisia annua. Issue 6 (12th April 2021) - Chen, Ruibing; Bu, Yuejuan; Ren, Junze; Pelot, Kyle A.; Hu, Xiangyang; Diao, Yong; Chen, Wansheng; Zerbe, Philipp; Zhang, Lei
Summary: Plants synthesize diverse diterpenoids with numerous functions in organ development and stress resistance. However, the role of diterpenoids in glandular trichome (GT) development and GT‐localized biosynthesis in plants remains unknown. Here, the identification of 10 diterpene synthases (diTPSs) revealed the diversity of diterpenoid biosynthesis in Artemisia annua . Protein–protein interactions (PPIs) between Aa KSL1 and Aa CPS2 in the plastids highlighted their potential functions in modulating metabolic flux to gibberellins (GAs) or ent‐ isopimara‐7, 15‐diene‐derived metabolites (IDMs) through metabolic engineering. A phenotypic analysis of transgenic plants suggested a complex repertoire of diterpenoids in Artemisia annua with important roles in GT formation, artemisinin accumulation and stress resilience. Metabolic engineering of diterpenoids simultaneously increased the artemisinin yield and stress resistance. Transcriptome and metabolic profiling suggested that bioactive GA4 /GA1 promote GT formation. Collectively, these results expand our knowledge of diterpenoids and show the potential of diterpenoids to simultaneously improve both the GT‐localized metabolite yield and stress resistance, in planta .